Archaeological data recovery in the Piceance and Wyoming basins of Northwestern Colorado and Southwestern Wyoming - Landt, Matthew J. (Archaeopress Publishing Ltd, 2018)
In 2008-9, a 14-in. natural gas liquids pipeline was constructed in Colorado and Wyoming. Alpine Archaeological Consultants, Inc. was hired to survey the route; the major research themes presented here synthesize chronometric and spatial information, subsistence, prehistoric technology, small cultural features, and prehistoric architecture.